Leveraging windows of opportunity for expertise to matter in global environmental governance: insights from the United Nations Convention to Combat Desertification - Velander, Sara; De Donà, Matteo (Frontiers in Climate, 2024)
Whether and under what conditions scientific knowledge provided by experts actually leads to political action is a question that academic research in various fields have focused on at length, without reaching a definitive answer. The position of expertise is especially delicate within the global environmental governance sphere containing multiple values, worldviews and epistemological standpoints.Methods: Firstly, we developed a theoretical model to examine how contextual factors, like institutional design and boundary work dynamics, contribute to expertise influencing global environmental governance. Secondly, we applied this model to the case of the Science Policy Interface to the United Nations Convention to Combat Desertification (UNCCD SPI), using data from semi-structured interviews with SPI stakeholders and participant observation of meetings.We identified specific dimensions of the SPI mandate that enabled expertise to matter: inclusive membership of practitioners, close interaction between experts and political actors, coordination with other advisory bodies, regular reviews, and a small group size. However, after underpinning the prevailing differences in power between SPI experts and member states in their interactions, we found that international environmental decision-making and its national-level implementation remain ultimately and inevitably subordinated to political actors, making it less likely for expertise to have a significant impact.Discussion: International expertise for sustainable development can only take advantage of the rare 'windows of opportunity' that intergovernmental processes concede for experts to influence policy.